Teaching of Chemistry and Visual Deficiency: mapping the research in CINTEDI(s) (2014-2020) (Research, Society and Development, 2021)
The objective of this research is to investigate how the process of academic records regarding teaching and learning Chemistry in relation to Visual Impairment is being triggered in CINTEDIs (2014-2020). We chose the mapping of publications records on the subject under study, explaining in a discursive way the data that, in our view, need to be explored by future research. For this, we specifically analyzed the thematic focus Curriculum Contents of the Chemistry discipline. We conclude that the study gap in this theme is huge, as the works are not able to address all High School and Higher Education Contents, bringing trend lines, already registered in the Brazilian context in other events, with the following contents: Hydrocarbons, Periodic Table and Blends, with specific focuses on creating inclusive teaching resources.